1998
DOI: 10.1172/jci3094
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with interferon-alpha preferentially reduces the capacity for amplification of granulocyte-macrophage progenitors (CFU-GM) from patients with chronic myeloid leukemia but spares normal CFU-GM.

Abstract: The biological target for interferon (IFN)-␣ in chronic myeloid leukemia (CML) is unknown, but one possibility is that amplification of granulocyte-macrophage colony-forming cells (CFU-GM) is reduced. Replating CFU-GM colonies and observing secondary colony formation provides a measure of CFU-GM amplification. Amplification of CML, but not normal, CFU-GM in vitro was significantly inhibited by IFN-␣ (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 27 publications
3
69
0
2
Order By: Relevance
“…At this concentration, neither the AUC of NBM nor that of CML CFU-GM was significantly reduced (Figure 2). In confirmation of previously reported results, 11 the AUC of NBM CFU-GM was not altered by growing the colonies in the presence of 100 U/ml IFN-␣ (100 ± 8.2% of controls; P = 0.9) whilst the AUC of CML CFU-GM was significantly reduced (60 ± 7% of controls; P = 0.03). When CFU-GM were grown in the presence of 0.5 ng/ml Ara-C + 100 U/ml IFN-␣, there was a significant reduction in the NBM AUC to 50 ± 10% of control values (P = 0.03) whereas for CML CFU-GM the addition of Ara-C to IFN-␣ did not further reduce the AUC.…”
Section: Cfu-gm Self-replicationsupporting
confidence: 91%
See 2 more Smart Citations
“…At this concentration, neither the AUC of NBM nor that of CML CFU-GM was significantly reduced (Figure 2). In confirmation of previously reported results, 11 the AUC of NBM CFU-GM was not altered by growing the colonies in the presence of 100 U/ml IFN-␣ (100 ± 8.2% of controls; P = 0.9) whilst the AUC of CML CFU-GM was significantly reduced (60 ± 7% of controls; P = 0.03). When CFU-GM were grown in the presence of 0.5 ng/ml Ara-C + 100 U/ml IFN-␣, there was a significant reduction in the NBM AUC to 50 ± 10% of control values (P = 0.03) whereas for CML CFU-GM the addition of Ara-C to IFN-␣ did not further reduce the AUC.…”
Section: Cfu-gm Self-replicationsupporting
confidence: 91%
“…11 This finding provided the first evidence for a selective inhibitory effect of IFN-␣ on CML progenitor cell kinetics. More recently, we have found that the tyrosine kinase inhibitor, STI571, also preferentially suppresses the replating ability of CML CFU-GM.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…31 This idea led us to establish the CFU-GM replating assay in order to measure the self-renewal of CFU-GM in various circumstances. 33 The increased replating ability of CFU-GM in PBPC harvests, compared with bone marrow CFU-GM, is therefore consistent with the more rapid rate of neutrophil recovery in recipients of PBPC since whilst a shift in emphasis to self-renewal at progenitor level would briefly reduce the emergence of neutrophils, the amplification potential between CFU-GM and neutrophil is such that even small numerical changes in the progenitor population can have a very large effect on neutrophil output.…”
Section: Discussionmentioning
confidence: 69%
“…[30][31][32] We have developed in vitro assays to measure the balance between self-renewal and differentiation of haemopoietic progenitor cells. These are based on secondary colony formation by replated CFU-GM colonies for the myeloid lineage; 33 for the erythroid lineage, the assay is based on subcolony formation during erythroid burst formation. 34 Using these assays, we have demonstrated that selfrenewal in both the erythroid and myeloid progenitor populations varies according to tissue source and is modulated by external factors such as cytokines.…”
mentioning
confidence: 99%